2021
DOI: 10.1111/epi.17138
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine take‐up rate and safety in adults with epilepsy: Data from a multicenter study in China

Abstract: SummaryObjectiveThis study was undertaken to investigate the COVID‐19 vaccine uptake rate and possible postvaccination effects in adults with epilepsy.MethodsWe invited adults with epilepsy attending three centers in China from July 24 to August 31, 2021 to participate in this study. We also asked age‐ and sex‐matched controls among people attending for other chronic neuropsychiatric conditions and healthy controls accompanying people with illness attending the hospitals to participate. We excluded people who,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(106 citation statements)
references
References 7 publications
11
93
1
1
Order By: Relevance
“…In a study of the COVID-19 vaccine take-up rate in 491 adult patients with epilepsy from China (conducted in August 2021), 42% of those with epilepsy had had the first dose of a vaccine, compared with 93% of the controls and 84% of the people with other neuropsychiatric conditions (p < 0.0001). The main reasons for vaccine hesitancy were potential adverse effects of the vaccines and concerns about losing seizure control [9] ; these are similar to our observations. It is important to highlight that the incidence of the COVID-19 vaccine adverse events in the epilepsy group was similar to that in the controls in that Chinese study; they found no evidence suggesting seizure worsening after vaccination [9] .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In a study of the COVID-19 vaccine take-up rate in 491 adult patients with epilepsy from China (conducted in August 2021), 42% of those with epilepsy had had the first dose of a vaccine, compared with 93% of the controls and 84% of the people with other neuropsychiatric conditions (p < 0.0001). The main reasons for vaccine hesitancy were potential adverse effects of the vaccines and concerns about losing seizure control [9] ; these are similar to our observations. It is important to highlight that the incidence of the COVID-19 vaccine adverse events in the epilepsy group was similar to that in the controls in that Chinese study; they found no evidence suggesting seizure worsening after vaccination [9] .…”
Section: Discussionsupporting
confidence: 89%
“…The main reasons for vaccine hesitancy were potential adverse effects of the vaccines and concerns about losing seizure control [9] ; these are similar to our observations. It is important to highlight that the incidence of the COVID-19 vaccine adverse events in the epilepsy group was similar to that in the controls in that Chinese study; they found no evidence suggesting seizure worsening after vaccination [9] . In another study of 111 PWE from Kuwait (conducted in April 2021), COVID-19 vaccines showed a good safety profile and a low risk of epilepsy worsening [10] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this context, seizures were a common manifestation in post-vaccination relapses and always occurred in patients with a known history of epilepsy. Since an increase in seizure frequency after vaccination has also been reported in a minority of patients with non-autoimmune epilepsy, the possibility that systemic/structural rather than autoimmune factors might be the leading cause of this post-vaccine symptom should be considered ( Steriade et al, 2020 , Lu et al, 2022 ). The association between pre-vaccination disease severity, which represents a risk factor for remote symptomatic seizures, and the occurrence of post-vaccination worsening further reinforces this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…51 최근 중국에서 조사한 연구에서도 뇌전증 환자(42%)는 다른 정신질환 (84%)이나 건강한 대조군(93%)에 비해 백신 접종률이 낮았고, 난 치성 뇌전증 환자들이 조절되는 뇌전증 환자에 비해 유의하게 접 종률이 낮았다. 52 의료진을 대상으로 한 설문에서도 약 74% 정도 만이 뇌전증 환자에게 백신 접종을 추천하겠다고 하였다. 53 그러나 실제 COVID-19 백신 접종을 한 환자를 대상으로 한 연구에서 1차 접종을 한 54명 뇌전증 환자(18세 이상) 중 1명만 이 발작이 악화되었고, 30% 정도에서 두통, 피로, 발열 등 일반 적 인 백 신 부작 용 만 이 있었 다.…”
Section: 뇌전증 환자에서의 Covid-19 백신unclassified